Cooling performance optimization of air cooling lithium-ion battery thermal management system based on multiple secondary outlets and baffle. (1st August 2022) - Zhang, Furen; Liu, Peiwen; He, Yanxiao; Li, Shiyuan
Abstract: Air cooling has attracted extensive attention in the field of battery thermal management (BTMS). A comprehensive optimization scheme adding secondary outlets and baffle was proposed in this paper to improve the cooling performance of the BTMS. Computational fluid dynamics (CFD) was conducted to investigate the influences of the number and width of secondary outlets and baffles on the cooling performance of the BTMS. The effectiveness of CFD method was verified by the air cooling heat dissipation experiment of battery pack. Firstly, the effects of the number and width of the secondary outlets were discussed and optimized. The results showed that, comparing with the initial Z-type BTMS, the maximum temperature (Tmax ) and the maximum temperature difference (ΔTmax ) were reduced by 1.84 °C (4.20%) and 3.66 °C (75%) after optimization, respectively. Then, based on the above optimization model, a baffle had been added in the cooling channel to further better the air volume distribution and enhance the cooling performance. Compared with the initial Z-type BTMS, Tmax of the optimum model was reduced by 2.17 °C (4.95%) and ΔTmax was reduced by 4.49 °C (91.89%). It can be seen that the optimization method proposed in this paper could be used to design the BTMS for electric vehicle. Highlights: The number and width of secondary outlets affected cooling performance greatly. The relative errors between experimental and simulation results were within 2.6%. The baffle could greatly improve the airflow distribution in local cooling channels. The maximum temperature was reduced by 2.17 °C (4.95%) after optimization. The maximum temperature difference was reduced by 4.49 °C (91.89%) after optimization.